2017
DOI: 10.1111/1365-2435.12889
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopes in tropical tree rings: theory, methods and applications

Abstract: Summary1. The notion that many tropical tree species form annual growth rings has triggered research on their growth and its environmental drivers over long periods of time. Even more recently, a large number of studies have also analysed the natural abundance of stable isotopes in tropical tree rings. The rapid developments in this young field call for a review. Here, we focus on stable isotopes of carbon ( 13 C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 143 publications
(347 reference statements)
0
34
0
5
Order By: Relevance
“…Nonetheless, rainfall is a strong predictor of dW/dc a across long-term studies (e.g., Fig. 1), as well as within shorter-term and individual studies 41 of tropical forests.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Nonetheless, rainfall is a strong predictor of dW/dc a across long-term studies (e.g., Fig. 1), as well as within shorter-term and individual studies 41 of tropical forests.…”
Section: Discussionmentioning
confidence: 90%
“…3038 ), as well as leaf-level studies 14,15 strongly support shown long-term patterns (including the influence of rainfall; see ref. 41 for a summary of effects of rainfall on W within individual studies of both ring-forming and ringless trees).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, long‐WUE was increased significantly under N addition (Figure 3). The long‐WUE captures variability in availability of other resources such as light, nutrients, and water, which is not the case for the instantaneous measure (Farquhar et al, 1989; van der Sleen, Zuidema, & Pons, 2017). Nonetheless, long‐WUE was enhanced slightly by 2.5%, indicating a minor if any impact of N addition on plant carbon–water relations.…”
Section: Discussionmentioning
confidence: 99%
“…These residual correlations most likely reflect higher-frequency effects, such as the common utilization of stored carbohydrate pools or stored soil water pools within the same year. The common use of resources would introduce interseasonal lags in the influence of climate on observed patterns in iWUE, g s and A (Helle & Schleser, 2004;Kimak & Leuenberger, 2015;Kress et al, 2009;Labotka et al, 2016;Leavitt, 2010;Sargeant & Singer, 2016;Vaganov et al, 2009). The linear regression approach that we applied to the EW1 and LW time series was effective in distinguishing sites that show clear evidence of seasonal dependence of isotope ratios on climate.…”
Section: Seasonal Relationships Obscured By Seasonal Lagsmentioning
confidence: 99%
“…Most often, tree-ring stable-isotope analysis is used to study interannual and decadal scale relationships between climate and carbon/water cycling (Bale et al, 2011;Leavitt, 2002;Roden & Ehleringer, 2007;Treydte et al, 2007;Wright & Leavitt, 2006). However, more finely resolved temporal-scale analyses, such as those utilizing the earlywood (EW) and latewood (LW) portions of annual rings, have also been used Fritts, 1976;Griffin et al, 2013;Kerhoulas, Kolb, & Koch, 2017;Labotka, Grissino-Mayer, Mora, & Johnson, 2016;Leavitt, 2002;Meko & Baisan, 2001;Ogée et al, 2009;Pellizzari, Camarero, Gazol, Sangüesa-Barreda, & Carrer, 2016;Sargeant & Singer, 2016;Szejner et al, 2016;Vaganov et al, 2009;Walcroft, Silvester, Whitehead, & Kelliher, 1997). At the onset of the growing season, cambial activity in conifer stems initiates xylogenesis forming earlywood (EW), which is usually characterized by large-diameter tracheids.…”
Section: Introductionmentioning
confidence: 99%